1996
DOI: 10.1172/jci118927
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of dexamethasone suppression of brain tumor-associated vascular permeability in rats. Involvement of the glucocorticoid receptor and vascular permeability factor.

Abstract: Brain tumor-associated cerebral edema arises because tumor capillaries lack normal blood-brain barrier function; vascular permeability factor (VPF, also known as vascular endothelial growth factor, VEGF) is a likely mediator of this phenomenon. Clinically, dexamethasone reduces brain tumor-associated vascular permeability through poorly understood mechanisms. Our goals were to determine if suppression of permeability by dexamethasone might involve inhibition of VPF action or expression, and if dexamethasone ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
0
6

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(154 citation statements)
references
References 65 publications
8
140
0
6
Order By: Relevance
“…In this study cells secreted VEGF in all conditions and although VEGF was slightly inhibited by Dex this recovered at later time‐points. Work has also indicated that Dex may inhibit VEGF (Heiss et al, 1996). The rising levels of VEGF indicate that if implanted, the cells in the scaffolds would support recruitment of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study cells secreted VEGF in all conditions and although VEGF was slightly inhibited by Dex this recovered at later time‐points. Work has also indicated that Dex may inhibit VEGF (Heiss et al, 1996). The rising levels of VEGF indicate that if implanted, the cells in the scaffolds would support recruitment of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wheals (5 mm in diameter) corresponding to the site of sample injection were individually resected and incubated in 100 AL of formamide at 37jC for 48 h to extract Evans blue dye. The amount of Evans blue dye was determined by measuring the absorbance at 660 nm in a spectrophotometer (31).…”
Section: Targeted Therapy Of Orthotopic Human Lung Cancermentioning
confidence: 99%
“…The role of dexamethasone in reducing peritumoural blood brain barrier permeability and inhibition of vascular endothelial growth factor action is well reported in the literature. 13 …”
Section: Discussionmentioning
confidence: 99%